1978
DOI: 10.1042/bj1700153
|View full text |Cite
|
Sign up to set email alerts
|

Glycerolipid biosynthesis in rat adipose tissue. Influence of adipose-cell size and site of adipose tissue on triacylglycerol formation in lean and obese rats

Abstract: The rates of lipid formation were compared in different fat-depots from lean and obese rats by using [14C]glycerol 3-phosphate, [14C]glucose or [14C]acetate as substrates. In lean animals, subcutaneous adipose tissue showed significantly lower rates of lipid synthesis than did perirenal and gonadal fat-tissue. In obese animals, the rates of lipid synthesis were significantly higher and did not vary from one fat-depot to another. Differences in the rates of lipid formation between lean and obese rats disappeare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0
2

Year Published

1979
1979
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 24 publications
2
20
0
2
Order By: Relevance
“…Protein concentrations were measured by the method of Bradford (30 (31,32). In brief, mice fed a HFD for 10 weeks were anesthetized, and a liver slice was taken from each mouse.…”
Section: Methodsmentioning
confidence: 99%
“…Protein concentrations were measured by the method of Bradford (30 (31,32). In brief, mice fed a HFD for 10 weeks were anesthetized, and a liver slice was taken from each mouse.…”
Section: Methodsmentioning
confidence: 99%
“…De novo lipogenesis activities were determined by the incorporation of [ 14 C]acetate into the lipids (16). Rat primary hepatocytes were plated in medium 199 and cultured overnight at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…For example, in rats, Jamdar et al [16] found higher rates of lipid formation using [14C]glycerol 3-phosphate,…”
Section: Introductionmentioning
confidence: 99%